2017
DOI: 10.2172/1427666
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Silver-Exchanged Mordenite and Silver-Functionalized Silica-Aerogel Under Vessel Off-gas Conditions

Abstract: US regulations 40 CFR 61, 40 CFR 190, and 10 CFR 20 govern release limits for volatile radionuclides contained in the gaseous effluents of used nuclear fuel (UNF) reprocessing facilities. Of the four volatile radionuclides that are restricted by the release limits ( 3 H, 14 C, 85 Kr, and 129 I) 129 I will require the greatest degree of abatement. Previous studies have shown that overall plant decontamination factor (DF) for 129 I must, at minimum, exceed 1,000 to meet regulatory requirements. Iodine-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 3 publications
1
52
0
Order By: Relevance
“…Comparison of Extended and Accelerated VOG Tests 29 May 2020 3 subsamples that represented 2-3% of a large deep bed and ~10% for subsamples that represent significantly larger fractions of thin beds (Jubin et al 2017). The error associated with NAA is presented in the figures of this report, but the effects of sample heterogeneity should be also be considered during data analysis.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparison of Extended and Accelerated VOG Tests 29 May 2020 3 subsamples that represented 2-3% of a large deep bed and ~10% for subsamples that represent significantly larger fractions of thin beds (Jubin et al 2017). The error associated with NAA is presented in the figures of this report, but the effects of sample heterogeneity should be also be considered during data analysis.…”
Section: Methodsmentioning
confidence: 97%
“…After these initial tests, more expansive experimentation evaluated the effects of concentration on CH 3 I adsorption by both AgZ and silver-functionalized silica aerogel (AgAero), an alternative silver-based iodine sorbent in early development (Jubin et al 2017). Concentrations from 40 to 1000 ppb v were evaluated and it was found that the adsorption profile in the bed was unchanged over that concentration range.…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent report (Jubin et al 2013), the role of off-gas pathways was examined since the gaseous radionuclides can partition to various different reprocessing off-gas streams. Based on this report and subsequent analysis (Jubin, et al 2015), the DF for 129 I could be 1000 to 3000. The required DF for H could be as high as 200, depending on the age of the fuel processed.…”
Section: Figuresmentioning
confidence: 93%
“…Multiple silver containing materials, including macroreticular resins, silver impregnated alumina, silver exchanged faujasite, hydrogen‐reduced silver exchanged mordenite (Ag 0 Z), and reduced silver‐functionalized silica aerogel (Ag 0 ‐Aerogel), have been developed and studied for I 2 and organic iodides adsorption 4,10,14‐18 . The reason for selecting silver‐containing materials over traditional liquid scrubbing methods is concluded to be stronger AgI bond and solid form, therefore, higher removal efficiency and lower operation cost 4,19‐22 .…”
Section: Introductionmentioning
confidence: 99%